#TITLE_ALTERNATIVE# - ANTONIO (NIM : 10107062); Pembimbing Tugas Akhir : Khreshna Imaduddin Ahmad Syuhada, M.Sc, Ph, FRANKY
Index is a statistic which can be used to measure human development. Index calculation can use order statistic concept and the odds function. The index used for measuring human development is known as Human Development Index. In measuring Human Development Index there are three used basic dimension of human development : 1. Healthy and having long life which are measured based on life expectancy at birth. 2. Knowledge which are measured based on adult literacy rates and gross enrollment rates in schools. 3. Descent standard of living which are measured based on household income rates. Life expectancy at birth and household income rates can be measured by implementing the approaches of linear regression model while adult literacy rates and gross enrollment rates in school can be measured by implementing the approaches of Binomial distribution. The unknown parameters appraisal in linear regression and Binomial distribution model is appraised by implementing Likelihood maximum methods.